Patient-centered outcomes for gastrointestinal cancer care: a scoping review protocol - Natalie G Coburn; Frances C Wright; Alyson L Mahar; Lesley Gotlib Conn; Julie Hallet; Amy T Hsu; Paul D James; Joanna Yang; Tori Barabash; Luckshi Rajendran; Claire Ludwig; Ekaterina Kosyachkova; et al. (BMJ Open)
Introduction Following a cancer diagnosis, patients and their caregivers face crucial decisions regarding goals of care and treatment, which have consequences that can persist throughout their cancer journey. To foster informed and value-driven treatment choices, evidence-based information on outcomes relevant to patients is needed. Traditionally, clinical studies have largely focused on a few concrete and easily measurable outcomes such as survival, disease progression and immediate treatment toxicities. These outcomes do not capture other important factors that patients consider when making treatment decisions. Patient-centred outcomes (PCOs) reflect the patients’ individual values, preferences, needs and circumstances that are essential to directing meaningful and informed healthcare discussions. Often, however, these outcomes are not included in research protocols in a standardised and practical fashion. This scoping review will summarise the existing literature on PCOs in gastrointestinal (GI) cancer care as well as the tools used to assess these outcomes. A comprehensive list of these PCOs will be generated for future efforts to develop a core outcome set.Methods and analysis This scoping review will follow Arksey and O’Malley’s expanded framework for scoping reviews. We will systematically search Medline, Embase, CINAHL, Cochrane Library and APA PsycINFO databases for studies examining PCOs in the context of GI cancer. We will include studies published in or after the year 2000 up to the date of the final searches, with no language restrictions. Studies involving adult patients with GI cancers and discussion of any PCOs will be included. Opinion pieces, protocols, case reports and abstracts will be excluded. Two authors will independently perform two rounds of screening to select studies for inclusion. The data from full texts will be extracted, charted and summarised both quantitatively and qualitatively.Ethics and dissemination No ethics approval is required for this scoping review. Results will be disseminated through scientific publication and presentation at relevant conferences.